ORIENTASI MORAL KEADILAN DAN ORIENTASI MORAL KEPEDULIAN: SUATUKECENDERUNGANPERBEDAAN ANTARA PENALARAN MORAL LAKI-LAKI DAN PEREMPUAN BERBEDA - Pratiwi Wahyu Widiarti (Jurnal Cakrawala Pendidikan, 2003)
In the long history of developmental psychology and especiallythat related to moral development, Kohlberg has been considered theforemost developerof moral studies although some great thinkersbefore him has inspired him. Along withG.H. Mead's and Baldwin'stheories, Piaget's theories have influenced him the most.Kohlberg has been influencedby Piaget especially in his twobasic ideasof cognitive and sequential mental structure. He hasdefined moralityas a structure of justice, in which the end of anymoral action, guidance, and sanction should guarantee individualjustice. This moral conceptof justice implies emphasis on humanconditions like equality, freedom, reciprocity, and appreciation.oflife. Truth is universal to all. In addition, Kohlberg has stated that theessential moral principle is thatthe principle ofjustice and this is thereason for any actionso that Kohlberg gives more emphasis on thedevelopmentof moral reasoning. The development of moralreasoning requires the occurrenceof cognitive development, socialrole-taking, and socio-cognitive conflict.In the course of developing his theories, Kohlberg has beenfaced with some criticism, especially on his measurements, which,when appliedto women, tend to place them on low-stage positions